Loss of a chloroplast encoded function could influence species range in kelp. Issue 15 (9th July 2019) - Rana, Shivani; Valentin, Klaus; Bartsch, Inka; Glöckner, Gernot
Abstract: Kelps are important providers and constituents of marine ecological niches, the coastal kelp forests. Kelp species have differing distribution ranges, but mainly thrive in temperate and arctic regions. Although the principal factors determining biogeographic distribution ranges are known, genomics could provide additional answers to this question. We sequenced DNA from two Laminaria species with contrasting distribution ranges, Laminaria digitata and Laminaria solidungula . Laminaria digitata is found in the Northern Atlantic with a southern boundary in Brittany (France) or Massachusetts (USA) and a northern boundary in the Arctic, whereas L. solidungula is endemic to the Arctic only. From the raw reads of DNA, we reconstructed both chloroplast genomes and annotated them. A concatenated data set of all available brown algae chloroplast sequences was used for the calculation of a robust phylogeny, and sequence variations were analyzed. The two Laminaria chloroplast genomes are collinear to previously analyzed kelp chloroplast genomes with important exceptions. Rearrangements at the inverted repeat regions led to the pseudogenization of ycf 37 in L. solidungula, a gene possibly required under high light conditions. This defunct gene might be one of the reasons why the habitat range of L. solidungula is restricted to lowlight sublittoral sites in the Arctic. The inheritance pattern of single nucleotide polymorphisms suggests incomplete lineage sorting of chloroplast genomes in kelp species. Our analysis of kelp chloroplast genomes shows that not only evolutionary information could be gleaned from sequence data. Concomitantly, those sequences can also tell us something about the ecological conditions which are required for species well‐being. Abstract : Kelp species have partly distinct habitats. We found that pseudogenization of a chloroplast gene might influence this habitat range.